Swiping in a variety of Ontario French. (March 2020) - Ott, Dennis; Therrien, Raymond
Abstract: This paper documents the existence of swiping – that is, inversion of a wh -phrase and its associated preposition under sluicing – in a non-Germanic language. We discuss swiping in a variety of Ontario French (Lafontaine French, LFF), which shares some of the characteristics of its extensively-studied English counterpart (Ross 1969, Merchant 2002, among others). We offer a preliminary description of swiping in LFF and consider some implications of these novel facts for the theory of swiping and sluicing. We suggest that LFF swiping supports an analysis in terms of non-constituent deletion, as originally suggested by Ross (1969 ) in his seminal work on sluicing.